GAYA KOMUNIKASI KOMANDO PRESIDEN JOKOWI DALAM KONFRENSI PERS DI YOUTUBE SEKRETARIAT PRESIDEN - Kusuma, Elang Teja (Program Studi Ilmu Komunikasi Universitas Islam Majapahit, 2024)
The overall objective of this research is to elucidate and analyze President Jokowi's command communication style in press conferences on YouTube Sekretariat Presiden. Utilizing a multidimensional approach encompassing verbal, nonverbal, rhetorical, media interaction, and public response aspects, this study aims to provide a deeper insight into modern political communication within the context of Indonesian governance. The implications of this research include the potential development of more effective communication strategies for the government in the digital era, as well as an understanding of the role of social media in shaping public opinion and facilitating interactions between leaders and the public.